PERILAKU STRUKTUR GEDUNG 18 LANTAI DENGAN DINDING GESER SEBAGAI PENAHAN GAYA GEMPA (STUDI KASUS APARTEMEN DAN KONDOTEL MATARAM CITY YOGYAKARTA) - , PINTA ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta is a region with high seismic intensity. The structure of high-rise buildings located in this region should have sufficient stiffness so that no damage could harm users when earthquake occurred. The addition of shear wall structure is one way to increase stiffness of the building. This research is analyzing the capacity of structural elements and the influence of shear walls in high rise buildings, taking a case study at Mataram City Apartments and Condominium, Yogyakarta. The building consists of two towers. Each tower has 18 floors with a total height of 66.3 m. Dimension of column at the Basement 2 to the first floor is 900x900 mm while the dimension of column at the second floor until the eighteenth floor is 600x900 mm. The maximum distance between the columns is 8 m. Dimension of main beam is 350x650 mm and the dimension of stringer is 250x500 mm. Analytical calculations in this research based on technical data field, quality of materials, and the results of structural analysis with SAP2000. After that, this research will calculate strength of the structure. The analysis based on SNI 03-2847-2002, SNI 03-1726-2002, and the Uniform Building Code (UBC) 1997 Chapter 16 on Requirements Design Structure. Three modification of the shear wall layouts in this research are use to understanding about the effect of adding shear walls to the natural vibration time. Based on the analysis and calculation, the structure has adequate capacity to support the load with the natural vibration period of 1.831 seconds. Maximum allowable vibration time by SNI 03-1726-2002 is 3.24 seconds, while the Uniform Building Code (UBC) is 1.698 seconds. First model can decrease the natural vibration period of 1.53 % to 1.803 seconds with a drift reduction of 11.35 % in the x axis and 35.27 % in y axis. The second model can decrease the natural vibration period by 5.08 % to be 1.738 seconds with drift reduction is 20.73 % the x axis, 39.31 % and y axis. The merged models have the natural vibration structure of 1,667 seconds. Based on this research, it can be concluded that the addition of shear walls in buildings can increase the high level of structural stiffness as the decrease in the time natural vibration and reduces drift floor.